Relationships between Self-Efficacy and the Academic Procrastination Behaviour among University Students in Malaysia: A General Perspective - Zainudin Abu Bakar; Muhammad Umar Khan (Intelektual Pustaka Media Utama, 2016)
Procrastination behaviour is a common phenomenon among people. In educational setting it always related to the student academic performance. Past studies have shown that the tendency of student to procrastinate could affect their academic life. For example, studying in the last minute is a procrastination behaviour committed by the students. This study is conducted to explore the association between academic procrastination, self-efficacy and academic performance among university students in Malaysia. The finding showed that most students are prone to procrastinate in their academic life. However in most cases it appears that the procrastination behaviour does not affect the student’s academic performance. A similar situation also recorded where the self-efficacy does not affect the tendency for student to procrastinate in their academic activities. It is suggested that in improving the student performance at the university the direct and indirect factors should be addressed including the academic procrastination behaviours. It was concluded that the student’s academic performance is influenced not directly by procrastination behaviour but by other factors. Several suggestions and recommendations are also presented.